Acute toxicity of the bowel after stereotactic robotic radiotherapy for abdominopelvic oligometastases. (3rd April 2018) - Frelinghuysen, Michael; Schillemans, Wilco; Hol, Lieke; Verhoef, Cornelis; Hoogeman, Mischa; Nuyttens, Joost Jan
Abstract: Aim: To correlate dose-volume histogram (DVH) parameters with appearance of grade ≥2 acute and late gastrointestinal toxicity of stereotactic body radiotherapy (SBRT) in patients with abdominopelvic solitary or oligometastatic disease outside the liver. Material and methods: Acute and late bowel toxicity of 84 abdominopelvic oligometastatic patients was registered. A logistic regression was performed between different DVH parameters and presence of grade ≥2 acute and late toxicity. A Normal Tissue Complication Probability (NTCP) model was built with significant parameters to determine complication probabilities (CP). Results: Thirteen (15%) of 84 patients experienced of grade ≥2 acute toxicity, while 8 (10%) reported late toxicity complications. A significant relationship was found for EQD2 (V30Gy, V40Gy, V50Gy and V65Gy ) and grade ≥2 acute toxicity. Dmax and D2 were not significant. Late grade ≥2 toxicity was not significantly correlated with any DVH parameter. According to our NTCP model for V40Gy, an irradiated bowel volume of 10 cm 3 of V40Gy resulted in CP of grade ≥2 acute toxicity of less than 10%. Local control was 87% at 2 years and 82% at 5 years. Overall survival was 61% at 2 years and 32% at 5 years. Conclusions: After SBRT for abdominopelvic oligometastases, in general, the presence of acute and late toxicity was low. A significant relationship was found for V30Gy, V40Gy, V50Gy and V65Gy and grade ≥2 acute toxicity. We estimated acute complication probabilities per volume of irradiated bowel by V40Gy and V50Gy